Alterations of distributed neuronal network oscillations during acute pain in freely-moving mice - Ponsel, Simon; Zhang, Jiaojiao; Pilz, Maximilian; Yanovsky, Yevgenij; Brankačk, Jurij; Draguhn, Andreas (IBRO reports, 2020)
The experience of pain involves the activation of multiple brain areas. Pain-specific activity patterns within and between these local networks remain, however, largely unknown. We measured neuronal network oscillations in different relevant regions of the mouse brain during acute pain, induced by subcutaneous injection of capsaicin into the left hind paw. Field potentials were recorded from primary somatosensory cortex, anterior cingulate cortex (ACC), posterior insula, ventral posterolateral thalamic nucleus, parietal cortex, central nucleus of the amygdala and olfactory bulb. Analysis included power spectra of local signals as well as interregional coherences and cross-frequency coupling (CFC). Capsaicin injection caused hypersensitivity to mechanical stimuli for at least one hour. At the same time, CFC between low (1−12Hz) and fast frequencies (80−120Hz) was increased in the ACC, as well as interregional coherence of low frequency oscillations (< 30Hz) between several networks. However, these changes were not significant anymore after multiple comparison corrections. Using a variable selection method (elastic net) and a logistic regression classifier, however, the pain state was reliably predicted by combining parameters of power and coherence from various regions. Distinction between capsaicin and saline injection was also possible when data were restricted to frequencies <30Hz, as used in clinical electroencephalography (EEG). Our findings indicate that changes of distributed brain oscillations may provide a functional signature of acute pain or pain-related alterations in activity.